2019
DOI: 10.26803/ijlter.18.8.12
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Applying Religious Values through Online Problem-Based Learning among Undergraduate Students: A Quasi-Experimental Study

Abstract: Implementing religious value can develop good attitude and behaviour. It can be implemented in various ways such as in speech, behaviour, gesturing, comprehension and assessment. This study aimed to be establish the impact of applying religious values through online Problem-Based Learning among undergraduate students. A total of 81 students were involved in the study and were divided into treatment and control groups. In order to identify the effectiveness of the module in applying values, the quasi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Although the ministry has had modules and materials since 2010, the implementation and disclosure in schools is still not comprehensive [7]. According to previous studies, the effectiveness factors of a module are also influenced by the teaching materials and methods used [19,20]. In fact, a study by Ball [21] found that using out-of-date material limits information and does not help students think in the current context.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ministry has had modules and materials since 2010, the implementation and disclosure in schools is still not comprehensive [7]. According to previous studies, the effectiveness factors of a module are also influenced by the teaching materials and methods used [19,20]. In fact, a study by Ball [21] found that using out-of-date material limits information and does not help students think in the current context.…”
Section: Discussionmentioning
confidence: 99%
“…Bukan itu sahaja, institusi zakat juga dapat menggunakan infografik sebagai salah satu cara untuk menjawab sebarang persoalan atau kemusykilan yang diajukan oleh netizen. Bahkan, penyediaan sumber bahan bermaklumat secara dalam talian amatlah diperlukan seiring dengan perkembangan dunia digital pada hari ini (Nawi, Zakaria, Hashim Mahalle & Ren, 2020). Maklum balas yang berkala dan segera juga amat penting dalam menangani sebarang tanggapan negatif netizen di dalam talian.…”
Section: Kesimpulan and Cadanganunclassified
“…Bahan yang direkabentuk juga haruslah mempunyai kualiti yang baik dan bermutu agar dapat memastikan mesej yang disampaikan bergerak lebih jauh dalam media sosial. Pemilihan bahasa juga berperanan untuk menarik minat dan memberi pengaruh yang tinggi kepada pengguna terutamanya dalam media sosial (Ma'alip, 2015;Nawi & Zakaria, 2019). Tambahan juga, infografik juga boleh digunakan untuk berkongsi statistik agihan dan kutipan zakat terkini, agihan yang disalurkan, jumlah penerima atau asnaf telah memperoleh manfaat dan sebagainya.…”
Section: Kesimpulan and Cadanganunclassified